A critical analysis of three contentious elements of the South African general anti-avoidance rules - Berry, Jan-Paul (Department of Finance and Tax, 2025)
This research assignment critically analyses three contentious elements of the South African GAAR to enhance clarity in its interpretation and application. In Chapter 3, the focus is on the purpose requirement, investigating whether it pertains to the subjective purpose of the taxpayer or the objective purpose of the of the arrangement itself having regard to the relevant facts and circumstances. Drawing on historical precedents, SARS documents, sections 80A and 80G of the ITA and tax scholars' opinions, the analysis suggests that the courts must rely on the objective surrounding facts and circumstances of the transaction, whilst also taking into account the subjective purpose and ipse dixit of the taxpayer. Chapter 4 delves into the ‘misuse or abuse' test, exploring the Canadian GAAR, relevant case law and scholars' opinions in order to shed light on what the ‘misuse or abuse' test actually means and whether it should be retained in the GAAR at all or as it is worded currently. It contends that this test was introduced to prevent taxpayers from relying on excessively narrow or literal interpretations of the provisions of the ITA in conjuring up avoidance arrangements. However, the analysis suggests the ‘misuse or abuse' test is redundant, given the establishment of the modern approach in interpreting statutes, proposing its repeal to avoid confusion and controversy. In Chapter 5, the examination centers on the term ‘tax benefit' and the viability of the binary defence in proving that no tax benefit has resulted from an arrangement. Analysing ITC 1625 and Absa v CSARS, the research concludes that the binary defence can succeed if a taxpayer starts from a position in which, if he does not enter into any transactions or arrangements, no income in a taxable form would accrue to him. The binary defence is therefore viewed as context-dependent, and it cannot universally refute SARS's claim of a ‘tax benefit'. Overall, the research aims to provide insights into these key aspects of the South African GAAR, proposing nuanced interpretations and considerations for greater clarity in its implementation.